Green Extraction of Microcrystalline Cellulose from Cabbage Waste (Brassica Oleracea L.) Using Steam Explosion and Low-Concentration Chemical Treatment - Nesha Permata Syafira; Bramantyo Airlangga; Sumarno (IPTEK The Journal of Engineering, 2025)
The increasing generation of agricultural waste presents both environmental challenges and opportunities for the development of sustainable materials. This study explores the extraction of microcrystalline cellulose (MCC) from cabbage waste using a combination of steam explosion and low-concentration chemical treatments to optimize lignocellulose degradation. The process involved sequential delignification with NaOH, bleaching with NaOCl, and steam explosion applied to samples that had been soaked in oxalic acid at varying concentrations (0%–2%). After drying, the samples were analyzed using FTIR, XRD, and SEM to evaluate the extracted MCC product. The analytical results showed that the applied method significantly increased cellulose purity, from 31.05% in untreated fibers to 69.88% after steam explosion following soaking in 2% oxalic acid. FTIR analysis confirmed the removal of lignin and hemicellulose, while XRD analysis indicated an increase in crystallinity from 39% to 57%, suggesting improved structural integrity. SEM analysis revealed enhanced fiber separation and reduced particle size, indicating efficient defibrillation. These results highlight the potential of an environmentally friendly approach to producing high-quality MCC, supporting green chemistry principles and sustainable development goals (SDGs). eThe extracted MCC holds promising applications, particularly as a biopolymer for drug delivery systems, polymer composites, and food additives.